2017
DOI: 10.1515/geocart-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

On the estimation of physical height changes using GRACE satellite mission data – A case study of Central Europe

Abstract: Abstract:The dedicated gravity satellite missions, in particular the GRACE (Gravity Recovery and Climate Experiment) mission launched in 2002, provide unique data for studying temporal variations of mass distribution in the Earth's system, and thereby, the geometry and the gravity fi eld changes of the Earth. The main objective of this contribution is to estimate physical height (e.g. the orthometric/normal height) changes over Central Europe using GRACE satellite mission data as well as to analyse them and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Similar research was performed for Central Europe (Godah et al, 2017c). It was shown that physical height changes as a combination of temporal variations of height anomalies and vertical displacements reach up to 22.8 mm over the selected study area.…”
Section: Maintenance Of the Vertical Control In Polandsupporting
confidence: 72%
“…Similar research was performed for Central Europe (Godah et al, 2017c). It was shown that physical height changes as a combination of temporal variations of height anomalies and vertical displacements reach up to 22.8 mm over the selected study area.…”
Section: Maintenance Of the Vertical Control In Polandsupporting
confidence: 72%
“…The degree-1 and degree-2 harmonic coefficients of CSR RL06 GRACE-based Global Geopotential Models (GGMs) were replaced by degree-1 from the solution described in [50] and the degree-2 obtained from Satellite Laser Ranging (SLR) [51]. The DDK3 decorrelation filter [52] that compromises between reducing noise and keeping the signal [18], was utilized to reduce the noise included in CSR RL06 GRACE-based GGMs. Moreover, these GGMs were truncated at d/o 60 that corresponds to the spatial resolution of the DDK3 filter.…”
Section: Data and Methods Usedmentioning
confidence: 99%
“…On 22 May 2018, the GRACE Follow-On (GRACE-FO) satellite mission, designed for a nominal lifetime of five years, was launched for further monitoring temporal mass variations within the Earth's system [12]. Several authors demonstrated the usefulness of GRACE satellite mission data for investigating temporal variations of geoid/quasigeoid heights, e.g., [13][14][15][16][17][18][19]. Moreover, many authors have proved that the estimated vertical deformations of the Earth's surface using GRACE satellite mission data are in a good agreement with the corresponding ones determined from other space geodetic techniques such as GNSS on a global scale, e.g., [20][21][22], on a continental scale, e.g., [23,24] in Europe, as well as on a local/regional scale, e.g., [25,26] in the Amazon basin, [27] in the West Africa, [28] in the East Africa, [29] in Japan, [30] in Bangladesh, [31][32][33] in China, [34,35] in Tibet, [36,37] in Poland, [38] in Greenland, and [39][40][41][42] in the North America, and Very Long Baseline Interferometry (VLBI) The GRACE (Gravity Recovery and Climate Experiment [11]) satellite mission, operated in the years 2002-2017, provided unique data for the determination of temporal mass variations within the Earth system including temporal variations of hydrological masses on a global/regional scale.…”
Section: Introductionmentioning
confidence: 99%
“…The results of study of physical height changes over Central Europe indicate that in the period of 2004-2010, they reach up to 22.8 mm (Godah et al, 2017c). It was also shown that using the seasonal decomposition (SD) method they can be modelled with the accuracy of 1.4 mm.…”
Section: Temporal Variations Of the Gravity Field From Grace Datamentioning
confidence: 99%